THE CONCEPT OF PHYSICAL AND SPIRITUAL BALANCE IN STUDENTS WITHIN AL-FARABI’S PHILOSOPHY OF EDUCATION - Achmad Akbar Qomaru Zaman; Ahmad Dani Hasan; Rifqi Khairul Anam (International Journal of Multidisciplinary Reseach, 2026)
Education plays a vital role in developing human potential comprehensively, encompassing both physical and spiritual dimensions. However, contemporary educational practice tends to privilege cognitive and academic achievement, often at the expense of students’ physical, moral, and spiritual growth. Although a growing body of research has examined Al-Farabi’s educational philosophy, most studies address his thought in general terms and have not specifically analyzed how physical–spiritual balance is articulated within his conception of educational aims. This study addresses that gap by analyzing the concept of physical and spiritual balance (jasmani–rohani) within Al-Farabi’s philosophy of educational objectives and its relevance for contemporary education. Using a qualitative descriptive approach through library research, primary and secondary sources on Al-Farabi’s educational philosophy were analyzed using content analysis. The findings show that Al-Farabi conceived education as a path toward happiness (al-sa’adah), attained through the harmonious cultivation of all human faculties. Physical balance is realized through bodily health and the cultivation of practical skills, while spiritual balance is cultivated through moral formation, intellectual development, and the strengthening of spiritual values, oriented toward the formation of the virtuous human being (al-insan al-kamil) within the framework of the virtuous city (al-madinah al-fadilah). These findings resonate strongly with contemporary educational goals that emphasize the holistic development of learners. Al-Farabi’s thought therefore offers a philosophical foundation for building a more holistic, humanistic, and character-oriented education system, one capable of responding to the erosion of moral character and student mental health documented in current Indonesian education discourse.